The development of fatigue during match-play tennis. (25th March 2014) - Reid, Machar; Duffield, Rob
Abstract : Data describing the activity profile and physiological characteristics of tennis match-play are extensive. However, these data have generally provided descriptive accounts of the one-off match-play of amateur or lowly ranked professional players lasting <3 h. Accordingly, these research efforts have likely failed to fully capture the demands of Grand Slam tennis match-play, particularly in the men's game where matches can last >5 h. Furthermore, there is a distinct lack of evidence-based insight regarding the manifestation of fatigue within and between tennis matches, notwithstanding that skeletal muscle function has been reported to reduce following prolonged match-play. Moreover, it is evident that match-play evokes pronounced and prolonged physiological, neuromuscular and psychological perturbations that may be exacerbated with consecutive days of match-play. Separate to these internal load responses, a collection of non-uniform movement and technical performance changes are reported, though rarely from match-play data. Consequently, direct or causal links between altered physiological or muscle contractile function and subsequent match-play outcomes are lacking. Indeed, emerging evidence seems to infer that players adjust their game strategy, and the resultant execution of stroke play, to accommodate any such deterioration in physiological function. The purpose of this review was to discuss the available literature in terms of the physiological, mechanical and psychological responses that occur during prolonged match-play in the context of their likely effect on match-play performance.